PROGNOSIS OF GESTATIONAL CHORIOCARCINOMA AT KHYBER TEACHING HOSPITAL PESHAWAR - Izhar, Raisa; Nisa, Aziz -un- (Journal of Ayub Medical College Abbottabad, 2003)
Background: Choriocarcinoma is a highly malignant tumour which originates in developing trophoblast of pregnancy, most commonly following molar pregnancy. It is a potentially fatal disease, but current management protocols have turned the prognosis highly favourable. Methods: This study was done on patients with gestational choriocarcinoma presenting to Gynae-B unit of Khyber Teaching Hospital Peshawar, between May, 1996 to December, 1997, diagnosed on the basis of clinical course and elevated level of HCG. Metastatic evaluation of the disease was done to assign different risk groups to the patients before selecting appropriate chemotherapy regimen for each patient. Results of the therapy were monitored by serial estimation of HCG levels. Results: During this period 5 patients of choriocarcinoma were treated. In 2 (40%) cases choriocarcinoma developed after molar pregnancy whereas in 3 (60%) cases antecedent pregnancy resulted in spontaneous abortion. Four (80%) patients were from poor socioeconomic class, 3 (60%) were above 39 years of age and 4 (80%) were multiparous. Two patients (40%) were medium risk and 3 (60%) were high risk cases. There was no patient with low risk disease. EMA-CO (Etoposide, Methotrexate, Actinomycin-D, Cytocine, Oncovine) regimen was administered to all patients. Maximum number of cycles of chemotherapy given was 8. Only one patient developed drug resistance. Overall cure rate was 80% (4 patients survived out of 5 at two years’ follow-up). Conclusion: Prognosis of gestational choriocarcinoma is favourable provided the appropriate therapy is administered early in the course of disease. Provision of free medical care should be considered for these patients to save their lives. Key words: gestational choriocarcinoma, prognosis, chemotherapy.